(3CKQ GdSjGSGJ GdGbJUGOjI aj GOGA GdeUGQa GdJLGQjI (B/s - (3eRfGf agO, fUQ MehOs ((3YeGf(B: s (3OGQ UaGA ddfTQ h GdJhRjY(B, s, 2009)
(3GdebOeI(B-(3GdaUd GdChd (B: (3fXe Jbjje GdCOGA aj GdeUGQa GdJLGQjI (B: (3GdeHMK GdChd (B: (3Jbjje GdCOGA, eaGgje hefWdbGJ CSGSjI (B: (3Gdeaghe GdYGe dJbje GdCOGA hCfhGYg (B: (3CgejI Jbjje GdCOGA(B: (3CgOGa Jbjje GdCOGA (B: (3QcGFR Jbjje GdCOGA (B: (3eQGMd Jbjje GdCOGA (B: (3GdebheGJ GdCSGSjI dfXe Jbjje GdCOGA (B: (3GdYhGed GdeDKQI aj GNJjGQ fXGe Sdje dJbjje GdCOGA (B: (3GdeHMK GdKGfj (B: (3eOGNd Jbjje GdCOGA aj GdeUGQa GdJLGQjI (B: (3GdeOGNd GdeGdjI (B: (3eOGNd GdaGYdjI dJbjje GdCOGA (B: (3GdeOGNd GdYGeI ddJbjje (B: (3GdeHMK GdKGdK (B: (3eDTQGJ Jbjje GdCOGA aj GdeUGQa GdJLGQjI(B-(3GdaUd GdKGfj (B: (3GdSjGSGJ GdGbJUGOjI hCKQgG aj COGA GdeUGQa GdJLGQjI (B: (3GdeHMK GdChd (B: (3GdYdGbI GdJHGOdjI ddSjGSGJ GdGbJUGOjI hCOGA GdeUGQa GdJLGQjI (B: (3GdeHMK GdKGfj (B: (3GdSjGSGJ GdGbJUGOjI aj GdYQGb ddeOI (B(1980-2004) : (3GdeHMK GdKGdK (B: (3GdSjGSGJ GdGbJUGOjI aj GdCQOf ddeOI (B(1980-2004)-(3GdaUd GdKGdK (B: (3Jbjje COGA GdeUGQa GdJLGQjI aj HdOj GdOQGSI (B: (3GdeHMK GdChd (B: (3Jbjje COGA GdeUGQa GdJLGQjI GdYQGbjI YjfI GdOQGSI (B: (3GdeHMK GdKGfj (B: (3Jbjje COGA GdeUGQa GdJLGQjI GdCQOfjI YjfI GdOQGSI (B: (3GdeHMK GdKGdK (B: (3ebGQfI COGA GdeUGQa GdJLGQjI GdYQGbjI hGdCQOfjI(B-(3GdaUd GdQGHY (B: (3bjGS CKQ GdSjGSGJ GdGbJUGOjI aj COGA GdeUGQa GdJLGQjI aj HdOi GdOQGSI hJMdjdg (B: (3GdeHMK GdChd (B: (3HfGA GdfeGPL GdbjGSjI hJhUjagG (B: (3GdeHMK GdKGfj (B: (3bjGS CKQ GdSjGSGJ GdGbJUGOjI aj COGA GdeUGQa GdJLGQjI GdYQGbjI hGdCQOfjI (B: (3GdeHMK GdKGdK (B: (3JMdjd CKQ GdSjGSGJ GdGbJUGOjI aj COGA GdeUGQa GdJLGQjI GdYQGbjI hGdCQOfjI(B.s
(3HHdjhZQGajG(B: (3U(B.319s
Keywords: (3GdGbJUGO GdeGdjs; (3GdHfhc GdJLGQjIs